Земля русская: (в памяти живут люди) : [очерки] / Иван Васильев - Васильев Иван Афанасьевич (Лениздат, 1983)
Экземпляры: КХ (20121016) / Инвентарный номер: 794297 / Цена: 1.90 / Сис.шифр: Р2 / Авт.знак: В 19 / ГРНТИ: 17 / ББК: 84(2)